Thriving with Stone Age minds : evolutionary psychology, Christian faith, and the quest for human flourishing - Barret, Justin L., 1971-; King, Pamela Ebstyne, 1968- (Biologos books on science and Christianity, 2021)
"What does God's creation of humanity through the process of evolution mean for how we think about human flourishing? Combining scientific evidence with wisdom from the Bible and Christian theology, this introduction explores how the field of evolutionary psychology can be a powerful tool for understanding human nature and our distinctively human purpose"--